Prevalence of Pulmonary Tuberculosis Among HIV Infected Drug Users in Pokhara, Kaski, Nepal - Verma, SC; Dhungana, GP; Joshi, HS; Kunwar, HB; Jha, RK; Pokhrel, AK (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Introduction: Studies conducted in different countries suggest that HIV infected drug users have a higher chance of acquiring pulmonary tuberculosis (PTB) in comparison to general population. However, there is no information about the prevalence of PTB among HIV infected drug users in Nepal. Objectives: The main objectives of this study were to document the socio-demographic and behavioral attributes; clinical symptoms and prevalence of PTB in HIV infected drug users in Pokhara, Kaski, Nepal. Methods: In a cross-sectional study, we enrolled 62 HIV infected drug users not diagnosed with PTB in the past from five HIV care centers in Pokhara. Using questionnaire, first we documented participants’ socio-demographic and behavioral attributes and clinical symptoms. This was followed by tuberculosis testing in all enrolled participants at the Regional Tuberculosis Center (RTC) in Pokhara. Results: Of the 62 HIV infected drug users, PTB was diagnosed in 3 (4.8%) participants. All of them were male in the productive age group. Cough was the major clinical symptoms (54.8%) in the study participants. About 91.9% participants reported they had acquired HIV infection through injecting drug use. Buprenorphine/heroin was the major drug used (48.4%) for addiction. Conclusion: This study provides first evidence of prevalence of PTB in HIV infected drug users in Nepal. The findings suggest tuberculosis testing be conducted in HIV infected persons including the HIV infected drug users in Nepal. Early detection of PTB in HIV infected drug users may help to reduce the morbidity and mortality as well as spread of TB in the community. Keywords: Drug users; HIV/AIDS; Nepal; Pokhara; Tuberculosis DOI: 10.3126/saarctb.v7i2.4401 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 19-25